crisis and migratory strategies of social reproduction. an analysis from the study of ecuadorian migration in spain - Sanz Abad, Jesús (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2015)
Migratory paths are characterised by their changing character and by their constant breakdowns, transformations and recompositions depending on global circumstances and on social reproduction strategies developed by migrants. This paper analyses some strategies of social reproduction developed by migrants under economic crisis, starting from the analysis of Ecuadorian migration. We pay special attention to those aspects which are crucial for the construction of the migratory project and the forms in which the development of productive and reproductive strategies are linked in the domestic group. This text advocates the need to think the migratory project and the return in a united and comprehensive manner as a part of the same process. Finally, we highlight the importance of adopting an evolving perspective in the analysis of migrations.